2022
DOI: 10.2478/aoas-2021-0022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of in Vitro Rumen Methane Production by Three Statins

Abstract: The aim of this study was to evaluate the effects of increasing concentrations of three pure statins on in vitro methane production and rumen fermentation. The effects of atorvastatin, rosuvastatin and simvastatin at three concentrations (1, 10, and 100 mg/L of culture fluid) were evaluated using in vitro 24 h batch incubation of buffered rumen fluid with a 70:30 forage:concentrate substrate. All statins tested demonstrated the ability to reduce methanogenesis. Methane inhibition potential was decreasing in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It was reported that A. terreus could produce Lv with the concomitant formation of simvastatin as a secondary metabolite in submerged fermentation experiments of oat grain [ 11 ]. A remarkable feature of simvastatin (10 mg/L culture media) is that it reduced the in vitro methane production ( p < 0.05) of a diet containing 70% forage and 30% concentrate as a substrate and rumen fluid inoculum from Holstein cows [ 53 ]. Thus, the presence of simvastatin in the post-fermented oat straw could enhance its contribution to methane mitigation if used as a supplement for ruminants.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that A. terreus could produce Lv with the concomitant formation of simvastatin as a secondary metabolite in submerged fermentation experiments of oat grain [ 11 ]. A remarkable feature of simvastatin (10 mg/L culture media) is that it reduced the in vitro methane production ( p < 0.05) of a diet containing 70% forage and 30% concentrate as a substrate and rumen fluid inoculum from Holstein cows [ 53 ]. Thus, the presence of simvastatin in the post-fermented oat straw could enhance its contribution to methane mitigation if used as a supplement for ruminants.…”
Section: Resultsmentioning
confidence: 99%
“…The rumen fluid was collected before morning feeding and filtered with 2-layer cheesecloth into a 1-litre Schott Duran ® bottle with an oxygen-free headspace. The bottles were closed with valves kept in an open position by following the protocol of Joch et al (2022) to prevent CO 2 accumulation in the flask, which would cause the ruminal fluid's pH to drop and affect the microbial population. Then rumen fluid (inoculum medium) was transported to the laboratory under anaerobic conditions at 39°C.…”
Section: Ruminal Fluid Collectionmentioning
confidence: 99%
“…The effects of statins on methanogenesis and overall rumen fermentation vary depending on statin type and concentration. Hydrophobic statins, such as simvastatin and atorvastatin, seem to be more effective compared to the hydrophilic statins, such as rosuvastatin [61]. Several in vitro and in vivo studies have examined the potential of statins such as lovastatin and mevastatin to reduce rumen CH 4 production, but results were inconclusive [62,63].…”
Section: Statinsmentioning
confidence: 99%